The Use of Quizzes Application in Teaching Speaking to Indonesian English as Foreign Language (EFL) Students - Yanpitherszon Liunokas (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Learning motivation is one of the determining factors in achieving learning objectives. From learning motivation, students have a desire to take part in continuous learning. Therefore, a teacher must be able to increase student motivation in learning and there are many ways that teachers can use in increasing student learning motivation and one way to increase student motivation is by using media that is fun and easy for students to use. Quizizz is a learning application used by First semester students of the English Study Program of Nusa Cendana University, Kupang. . So, researchers conducted research on student perceptions of using the Quizizz application. The data collection techniques used by researchers are questionnaires and documentation. The results of this study indicate that the perceptions of students in First semester students of the English Study Program of Nusa Cendana University, Kupang. are motivated by the application of learning using the quizizz application. The quizizz application makes students happy to use it and find it easy to use.